Verbs of emotion with se in Slovene: between middle and reflexive semantics. A cognitive analysis - Agnieszka Będkowska-Kopczyk (Cognitive Studies | Études cognitives, 2014)
Verbs of emotion with se in Slovene: between middle and reflexive semantics. A cognitive analysis